The centenary and education: The epic of the nationality in debate - Rodríguez Aguilar, María Inés; Ruffo, Miguel José (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
It is presented a synthesis of the narrative of the pedagogical story from 1910, in the context of the celebration of the centenary of the events of May in relation with some themes that constitute the field of education: policy developments and the bureaucratic dynamics, the editorial practices, Protagonists nationalists managements and the alternative of other voices. As editing sources there were official reports and publications (memories and El Monitor Común), and ministerial messages, such as bibliography, texts and articles by specialists in the history of education and cultural studies.